Xinfeng Capsule inhibits oxidative stress via regulating the PPARγ/ Hmgcs2 signaling pathway in lung tissue of adjuvant arthritis rats - Zhang, Ping-Heng; Chen, En-Sheng; Liu, Jian; Xiao, Chang-Hong (Frontiers in Pharmacology, 2025)
BackgroundXinfeng Capsule (XFC) is a traditional Chinese medicine compound preparation that has been clinically used to treat rheumatoid arthritis (RA) for more than 20 years. It has demonstrated clear therapeutic effects, including improving pulmonary function and reducing lung injury in patients with RA. However, the precise mechanism underlying its protective effect against lung injury remains unclear. This study aims to explore the potential mechanisms of XFC in the treatment of lung injury.MethodsLiquid chromatography-mass spectrometry (LC-MS) analysis was conducted to determine the chemical composition of XFC. Proteomic and bioinformatic analyses of differentially expressed proteins (DEPs) in rat lung tissue were performed using tandem mass tag labeling. A rat adjuvant arthritis (AA) model was established using Freund’s complete adjuvant to observe pathological changes in synovial and lung tissues, as well as alterations in lung function. In addition, a cell model was constructed by inducing lung fibroblasts with transforming growth factor-β1 (TGF-β1) to investigate the effects of XFC-containing serum on oxidative stress and pulmonary fibrosis through the peroxisome proliferator-activated receptor gamma (PPARγ)/3-hydroxy-3-methylglutaryl-CoA synthase 2 (HMGCS2) pathway.ResultsLC-MS analysis identified a total of 867 compounds in XFC, of which 25 unique compounds were closely associated with pulmonary fibrosis and lung injury. Proteomic analysis suggested that XFC may regulate PPAR signaling pathway-related proteins and alleviate lung injury in AA rats. Animal experiments showed that XFC significantly inhibited immune inflammation, synovial hyperplasia, and oxidative stress in AA rats, while reducing lung injury and improving lung function. Furthermore, XFC-containing serum suppressed TGF-β1–induced proliferation of lung fibroblasts, promoted PPARγ expression, and significantly decreased the levels of interleukin-6, tumor necrosis factor-α, reactive oxygen species, nicotinamide adenine dinucleotide phosphate oxidase 4, HMGCS2, collagen type I α 1, collagen type III α 1, and α-smooth muscle actin (P < 0.01). In addition, XFC partially reversed the effects of the PPARγ antagonist GW9662, activated the PPARγ signaling pathway, inhibited oxidative stress and inflammatory responses, and exerted anti-fibrotic effects similar to those of the PPARγ agonist rosiglitazone.ConclusionXFC inhibits inflammation and oxidative stress by regulating the PPARγ/HMGCS2 pathway, thereby attenuating fibrosis and alleviating lung injury.